Pathological complete response after afatinib treatment of stage IV oligometastatic adenocarcinoma of the lung: the role of pulmonary surgery - Ping-Chung Tsai; Yi-Chen Yeh; Chien-Sheng Huang; Chao-Hua Chiu (Surgical Case Reports)
Abstract Background Some oligometastatic lung cancer patients, after induction systemic chemotherapy or tyrosine kinases inhibitor treatment, followed by aggressive radical consolidative treatment, have improved overall survival. Unfortunately, clinical criteria cannot assess such patients. Case presentation We hereby reported the case of a 55-year-old female with lower back pain and bilateral lower leg numbness for months and who had an osteolytic bone lesion over the third lumbar vertebra. In February 2017, a third lumbar vertebra biopsy showed metastatic adenocarcinoma, compatible with lung origin (thyroid transcription factor-1 positive [TTF-1], L858R mutation positive). Complete imaging of the right lower lobe (RLL) showed a spiculated mass of about 3.4 × 2.2 cm, and a trans-bronchoscopic lung biopsy revealed non-small cell carcinoma of lung origin (positive for TTF-1 and negative for p40). Tentative diagnosis was RLL adenocarcinoma, cT2aN0M1b, with bone metastasis at L3. The epidermal growth factor receptor-tyrosine kinase inhibitor afatinib was prescribed beginning April 2017. A November 2018 follow-up CT scan showed regression in the RLL lung mass. A whole-body positron emission tomography-computed tomography showed RLL lung nodule with faint uptake and mildly increased uptake in the L3 vertebra. After providing informed consent, the patient received uniportal video-assisted thoracoscopic RLL lobectomy and radical mediastinal lymph node dissection on December 25, 2018. The final pathology report was fibrotic scar with no residual tumor cells, compatible with post-treatment status, ypT0N0. Curative intent radiotherapy was also applied to the L3 vertebra after the operation. The patient is still alive for more than 32 months after initially diagnosed with metastatic lung adenocarcinoma. Conclusions Our case provides additional data to support that tissue assessment through primary lung tumor resection after systemic treatment of oligometastic lung cancer by minimally invasive surgery can reveal the treatment effect and potentially provide a surrogate endpoint in further clinical trials.